PENGARUH EKUITAS MEREK, KUALITAS PELAYANAN, DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN - Rismiati, Cicik; Siagian, Riduan; Gagarin, U.Heri (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The purpose of this study was to determine the customer satification in shaping customer loyalty. The research method using Structural Equation Modeling (SEM). This research is a quantitative method of sampling nonprobability determination using incidental sampling. The results showed that the quality of service a significant effect on customer satisfaction, brand equity and product quality did not significantly affect customer satisfaction. While on customer loyalty, brand equity, quality of service, and the quality of the product showed a significant influence.